Serous cystic neoplasm of the pancreas: a multinational study of 2622 patients under the auspices of the International Association of Pancreatology and European Pancreatic Club (European Study Group on Cystic Tumors of the Pancreas). Issue 2 (4th June 2015) - Jais, B; Rebours, V; Malleo, G; Salvia, R; Fontana, M; Maggino, L; Bassi, C; Manfredi, R; Moran, R; Lennon, A M; Zaheer, A; Wolfgang, C; et al.
Abstract : Objectives: Serous cystic neoplasm (SCN) is a cystic neoplasm of the pancreas whose natural history is poorly known. The purpose of the study was to attempt to describe the natural history of SCN, including the specific mortality. Design: Retrospective multinational study including SCN diagnosed between 1990 and 2014. Results: 2622 patients were included. Seventy-four per cent were women, and median age at diagnosis was 58 years (16–99). Patients presented with non-specific abdominal pain (27%), pancreaticobiliary symptoms (9%), diabetes mellitus (5%), other symptoms (4%) and/or were asymptomatic (61%). Fifty-two per cent of patients were operated on during the first year after diagnosis (median size: 40 mm (2–200)), 9% had resection beyond 1 year of follow-up (3 years (1–20), size at diagnosis: 25 mm (4–140)) and 39% had no surgery (3.6 years (1–23), 25.5 mm (1–200)). Surgical indications were (not exclusive) uncertain diagnosis (60%), symptoms (23%), size increase (12%), large size (6%) and adjacent organ compression (5%). In patients followed beyond 1 year (n=1271), size increased in 37% (growth rate: 4 mm/year), was stable in 57% and decreased in 6%. Three serous cystadenocarcinomas were recorded. Postoperative mortality was 0.6% (n=10), and SCN's related mortality was 0.1% (n=1). Conclusions: After a 3-year follow-up, clinical relevant symptoms occurred in a very small proportion of patients and size slowly increased in less than half. Surgical treatment should be proposed only for diagnosis remaining uncertain after complete workup, significant and related symptoms or exceptionally when exists concern with malignancy. This study supports an initial conservative management in the majority of patients with SCN. Trial registration number: IRB 00006477.